If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + -4)(2x + 3) = 0 Reorder the terms: (-4 + 3x)(2x + 3) = 0 Reorder the terms: (-4 + 3x)(3 + 2x) = 0 Multiply (-4 + 3x) * (3 + 2x) (-4(3 + 2x) + 3x * (3 + 2x)) = 0 ((3 * -4 + 2x * -4) + 3x * (3 + 2x)) = 0 ((-12 + -8x) + 3x * (3 + 2x)) = 0 (-12 + -8x + (3 * 3x + 2x * 3x)) = 0 (-12 + -8x + (9x + 6x2)) = 0 Combine like terms: -8x + 9x = 1x (-12 + 1x + 6x2) = 0 Solving -12 + 1x + 6x2 = 0 Solving for variable 'x'. Factor a trinomial. (-3 + -2x)(4 + -3x) = 0Subproblem 1
Set the factor '(-3 + -2x)' equal to zero and attempt to solve: Simplifying -3 + -2x = 0 Solving -3 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -2x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -2x = 0 + 3 -2x = 0 + 3 Combine like terms: 0 + 3 = 3 -2x = 3 Divide each side by '-2'. x = -1.5 Simplifying x = -1.5Subproblem 2
Set the factor '(4 + -3x)' equal to zero and attempt to solve: Simplifying 4 + -3x = 0 Solving 4 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -3x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -3x = 0 + -4 -3x = 0 + -4 Combine like terms: 0 + -4 = -4 -3x = -4 Divide each side by '-3'. x = 1.333333333 Simplifying x = 1.333333333Solution
x = {-1.5, 1.333333333}
| x=137-173 | | 173-137= | | 17-x=1/3(21) | | 3t-8/2=4t | | 4m^2-11m-45=0 | | 3t-9/2 | | 7.2*10^4/9.4*10^-11 | | 5w+9.9=4.9+8w | | 5m^2-34m-48=0 | | 3(x+2)+27=60 | | x+2/x-3 | | (3x^2-5x-6)+(5x^2+4x+4)= | | 7y^2+51=0 | | 1.2(b-10)=50 | | 4+3x=8x+24 | | 4t+14=6t/5 | | 7x-3=4x-9 | | 5x-12/-3=-6 | | 7w-3w=2(3w+11) | | -6=m-2 | | 82=-2+6(v+6) | | -6=m | | 4y+7y=-99 | | -3=n | | 4a+6=90 | | m-3=21 | | -2y+5.2x=2 | | Y=5-10.3x | | (8x-1)(x^2-4x+1)= | | y=-80/7/-4 | | -80/7/-4 | | 16=x-4y |